2008
DOI: 10.1002/cphc.200800144
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Investigation of the OH.‐Initiated Oxidation of Benzaldehyde in the Troposphere

Abstract: A mechanistic and kinetic study of the OH(*)-initiated oxidation of benzaldehyde is carried out using quantum chemical methods and classical transition state theory. We calculate the rate constant for this reaction within the temperature range of 200-350 K at atmospheric pressure. All possible hydrogen abstraction and OH(*) addition channels are considered and branching ratios are obtained. Tunneling corrections are taken into account for abstraction channels, assuming unsymmetrical Eckart barriers. The aldehy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Therefore (and according to Hammond’s postulate) there must be a direct relation between the L value and the heat of reaction of a specific pathway. Since deviations from this postulate have previously been reported for other systems, we decided to verify if the reactions studied in the present work are in line with the rule or with the exceptions. Figure A shows that, in general, HAT mechanisms involving carotenoids and the OOH free radical obey Hammond’s postulate, i.e., the earlier the transition state the more exothermic the reaction.…”
Section: Resultsmentioning
confidence: 58%
“…Therefore (and according to Hammond’s postulate) there must be a direct relation between the L value and the heat of reaction of a specific pathway. Since deviations from this postulate have previously been reported for other systems, we decided to verify if the reactions studied in the present work are in line with the rule or with the exceptions. Figure A shows that, in general, HAT mechanisms involving carotenoids and the OOH free radical obey Hammond’s postulate, i.e., the earlier the transition state the more exothermic the reaction.…”
Section: Resultsmentioning
confidence: 58%
“…Thus, the earliness of the TSs can be directly inferred from the forming C· · ·F distance. That is, the longer the C· · ·F distance is, the earlier the TS is (Iuga et al, 2008). Figure S2 showed that the F-TS add-Cl pathway was the earliest among three addition TSs, suggesting that this pathway was more exothermic than the F-R add-F and F-R add-Br pathways according to the Hammond postulate (Hammond, 1955).…”
Section: X-addition Pathwaysmentioning
confidence: 98%
“…Table 3 and Figure 2(b) show that channel (8) is exothermic by 11.02 kcal mol -1 and channel (9) is endothermic by 18.53 kcal mol -1 , inconsistent with Hammond's postulate. Deviations from Hammond's postulate have previously been observed for other systems [40,41]. Due to the existence of the hydrogen bond in TS7, channel (7) has a lower barrier height, with 41.18 kcal mol -1 than channels (8) and (9) with 41.78 and 43.98 kcal mol -1 , respectively.…”
Section: Attack On the Carbon Atom Perpendicular To C -C Bond Axismentioning
confidence: 76%